Expectations hypothesis and theory of inflation - appraisal - Mulvey, C; Trevithick JA (Economic & Social Studies, 1972)
One of the most interesting and significant developments to have emerged in recent ..years from the discussion of the nature of the 'Phillips Curve' has centred around the role of expectations in the inflationary process. Quite apart from the importance of this issue for the theory of inflation, the debate on the role of expectations has great significance for economic policy at the moment since it calls into question the long-run stability of the inflation/unemployment trade-off relation. The purpose of .this paper is to review the most important contributions to the expectations debate to present them in a coherent and accessible form paying particular attention to the adaptive expectations hypothesis which has been extensively used in the literature on the subject.
Keywords: Inflation Theory